Friends, Family, and Foes: The Influence of Father's Social Networks. (May 2013) - Murphy, Alexandrea Danielle; Gordon, Derrick; Sherrod, Hans; Dancy, Victoria; Kershaw, Trace
Fathers can play an important role in child development and family functioning. However, little is known about the influence of paternal perceptions of fatherhood involvement or the influence of fathers' peer networks. We explored the network characteristics (density, closeness, and degree centrality) and peer norms regarding sex, fatherhood, and other risk behaviors of 52 urban adult males in New Haven, Connecticut. Results identify that engagement in high-risk sexual behavior was associated with fatherhood involvement, with 88% of less involved fathers engaging in high-risk sexual behavior ( p = .004). Denser networks were positively correlated with unfavorable peer norms such as cheating on a partner or drinking or using drugs ( p < .05). Our findings suggest that peer networks are important to father's health and behavior and that father's behaviors may be affected by peer norms. Interventions designed for men may be strengthened by including peers in programming and by addressing norms and norm changing.